Two fingerprinting sets for Humulus lupulus based on KASP and microsatellite markers - Driskill, Mandie; Pardee, Katie; Hummer, Kim E; Zurn, Jason D; Amundsen, Keenan; Wiles, Annette; Wiedow, Claudia; Patzak, Josef; Henning, John A; Bassil, Nahla V (PloS one, 2022)
Verification of clonal identity of hop (Humulus lupulus L.) cultivars within breeding programs and germplasm collections is vital to conserving genetic resources. Accurate and economic DNA-based tools are needed in dioecious hop to confirm identity and parentage, neither of which can be reliably determined from morphological observations. In this study, we developed two fingerprinting sets for hop: a 9-SSR fingerprinting set containing high-core repeats that can be run in a single PCR reaction and a kompetitive allele specific PCR (KASP) assay of 25 single nucleotide polymorphisms (SNPs). The SSR set contains a sex-linked primer pair, HI-AGA7, that was used to genotype 629 hop accessions from the US Department of Agriculture (USDA) National Clonal Germplasm Repository (NCGR), the USDA Forage Seed and Cereal Research (FSCR), and the University of Nebraska-Lincoln (UNL) collections. The SSR set identified unique genotypes except for 89 sets of synonymous samples. These synonyms included: cultivars with different designations, the same cultivars from different sources, heat-treated clones, and clonal variants. Population structure analysis clustered accessions into wild North American (WNA) and cultivated groups. Diversity was slightly higher in the cultivated samples due to larger sample size. Parentage and sib-ship analyses were used to identify true-to-type cultivars. The HI-AGA7 marker generated two male- and nine female-specific alleles among the cultivated and WNA samples. The SSR and KASP fingerprinting sets were compared in 190 samples consisting of cultivated and WNA accession for their ability to confirm identity and assess diversity and population structure. The SSR fingerprinting set distinguished cultivars, selections and WNA accessions while the KASP assays were unable to distinguish the WNA samples and had lower diversity estimates than the SSR set. Both fingerprinting sets are valuable tools for identity confirmation and parentage analysis in hop for different purposes. The 9-SSR assay is cost efficient when genotyping a small number of wild and cultivated hop samples (<96) while the KASP assay is easy to interpret and cost efficient for genotyping a large number of cultivated samples (multiples of 96).
Keywords: Phylogeny; Humulus; šlechtění rostlin; genotyp; Microsatellite Repeats; polymerázová řetězová reakce; Plant Breeding; Polymerase Chain Reaction; Alleles; Genetic Variation; alely; genetická variace; fylogeneze; mikrosatelitní repetice; Genotype